Screening of high β-glucosidase-producing yeast strains from the Penglai wine region (China) and their fermentation performances and aroma compositions in Petit Manseng wine fermentation - Tang, Xiao Hong; Ding, Yan; Zhong, Ke; Sun, Yu Xia; Han, Xiao Mei; Li, Zhi Yu; Li, Rui Rui (Frontiers in Microbiology, 2025)
The majority of aroma precursors in grapes exist as odorless glycosidic conjugates, which can be hydrolyzed by β-glucosidase to release free volatile aroma compounds, thereby enhancing the aromatic quality of wine. This study aimed to screen and characterize indigenous non-Saccharomyces cerevisiae strains with β-glucosidase activity for their potential to enhance terpenoid aroma compounds during wine fermentation. Grapes collected from 14 vineyard plots in the Penglai Wine Region (China) underwent spontaneous fermentation and yielded 203 single colonies. Among them, 85 strains of non-Saccharomyces cerevisiae were initially screened based on the geniposide chromogenic method, which were classified into 7 genera and 16 species. Nine high-performance strains were subsequently selected for small-scale fermentation trials using Petit Manseng grape juice. The physicochemical parameters of wines were analyzed by high-performance liquid chromatography (HPLC), while volatile aroma compounds were quantified using a headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry (HS-SPME-GC–MS). The results revealed that Starmerella bacillaris CGCD1-9, Pichia fermentans CGCD1-4, and Zygosaccharomyces bailii JDCD01 significantly enhanced glycerol production, which might contribute to improved wine sensory quality. Four Hanseniaspora yeast strains exhibited the ability to increase ethyl acetate content. Among these strains, Hanseniaspora vineae CGCD1-1, Hanseniaspora uvarum CGCD1-3, and Hanseniaspora opuntiae CGCD1-7 showed a pronounced tendency to elevate geraniol levels, whereas Hanseniaspora occidentalis CGCD1-5 selectively promoted the biosynthesis of β-damascenone and 2-furanmethyl acetate. Zygosaccharomyces bailii JDCD01 primarily increased the levels of isobutanol and phenylethyl alcohol, while also exhibiting a slight enhancement in terpenoid production. Notably, S. bacillaris CGCD1-9 significantly enhanced five key terpenoids, namely, linalool, geraniol, citronellol, α-terpineol, and nerolidol, yielding the highest total terpene content among all strains, while increasing the content of alcohols (less than JDCD01). In contrast, Issatchenkia terricola SIVE4101 and Metschnikowia andauensis LFSY0-17 showed preferential accumulation of β-damascenone and total furans, with the former also significantly increasing the acetate ester content. This study provides new ideas and theoretical support for r developing targeted co-inoculation protocols with S. cerevisiae to achieve precise modulation of wine terpenoid profiles.